Experimental Application of the Italian Bridge Guidelines to a Stock of Prestressed Concrete Bridges - Andrea Floridia; Davide Messina; Dario Panarelli; Antonino Recupero; Pier Paolo Rossi; Nino Spinella (Infrastructures)
This study applies the first three levels of analysis outlined in the recent Italian Bridge Guidelines to a stock of prestressed concrete bridges located along the highways connecting the cities of Palermo, Messina and Catania in Sicily, south of Italy. The examined levels of analysis include census, visual inspection and determination of the structural–foundational and seismic Classes of Attention of bridges and viaducts. Data of the census and visual inspection activities were gathered using a custom-made web application. The details, the methodologies and all the features implemented in the web platform were illustrated and discussed. Furthermore, the collected data were described and critically analyzed, offering insights into the strength and limitations of each of the three examined levels of analysis of the Italian Bridge Guidelines. Finally, based on the detected defects and their numerousness with respect to the total number of assessed bridges, the authors proposed a straightforward and practical methodology for prioritizing any subsequent repairing intervention on specific groups of bridges.